Complying with the requirements for issuance of SRI sukuk: the case of Khazanah’s Sukuk Ihsan - Noordin, Nazrul Hazizi; Haron, Siti Nurah; Hasan, Aznan; Hassan, Rusni (Emerald Group Publishing Ltd., 2018)
Purpose – The purpose of this study is to provide a critical review on how the Khazanah’s Sukuk Ihsan was structured in compliance with the requirements for issuance of Sustainable and Responsible Investment (SRI) sukuk set by the Securities Commission (SC) Malaysia. Design/methodology/approach – To explain the structures and features of the Sukuk Ihsan, this study extracted important information from the sukuk’s Principle Terms and Conditions and Information Memorandum and presented them in a simple and easy-to-understand way. Next, this study refers to Part D: Requirement for Issuance, Offering or Invitation to Subscribe or Purchase Sustainable and Responsible Investment Sukuk of the SC’s Guidelines on Sukuk (revised edition: 28 August 2014) to assess the compliance of the sukuk in terms of eligibility of SRI sukuk issuer and SRI projects, use of proceeds, reporting and disclosure and independent assessment on SRI programmes. In addition, this study then compares the requirements stated in the SC’s SRI Sukuk Framework with the International Capital Market Association’s Green Bond Principles (GBP) and the USA’s Social Impact Bond (SIB) Act 2014. Findings – The present study finds that the definition of eligible SRI sukuk issuer in the Guidelines on Sukuk seems to be more stringent compared to the one provided in the GBP and the US’ SIB Act. Nevertheless, the SRI Sukuk Framework provides a more comprehensive yet precise list of eligible SRI projects, covering both environmental and social aspects, compared to the GBP (which only focuses on broad categories of environmental projects) and also the USA’s SIB Act (explicitly outlines 13 social projects which are aligned with the US Federal Government’s agenda in tackling social illnesses). Indeed, the main difference between the eligible SRI sukuk projects and its conventional counterparts lies in its compliance to Shariah principles. It is also observed that a significant emphasis has been given on SRI legislations in ensuring proper reporting and disclosure provided to the SRI sukuk stakeholders together with critical evaluation on the impacts of SRI programmes provided by an independent assessor. Practical implications – This paper contributes towards enriching the literature on the Islamic capital market, particularly on the integration between sukuk and social impacts investing. This paper was intended to highlight the important requirements in issuing SRI sukuk to various stakeholders of the Islamic capital market. Originality/value – The authors hope to shed some lights on the unique features and structural applications of SRI sukuk and its importance in becoming an effective instrument to raise funds for social agenda of a country by providing a real and practical example.